Implementing Fingerprint Attendance with Fuzzy Logic enhances employee attendance efficiency in a modern workplace - Ester Angeline Sitompul; Fiona Kharismatunnisaa; Yourdan Saputra; Riyo Putra Syam Satria; Nanda Octavia; Fiqri Nurfadilah; Muhammad Danang Mukti Darmawan; Firdayanti; Ivan De Nerol; Dhafa Kamil; Rafi Rasyid Parmana; Mohamad Alvin Renaldi (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
The implementation of fingerprint technology in attendance tools offers a cutting-edge solution for managing employee attendance in modern companies. This technology yields substantial advantages, such as enhanced operational efficiency, heightened precision, and reliable data security. The tool integrates advanced fingerprint sensor technology and fuzzy logic to identify employees and deliver more accurate attendance evaluations. The distinctiveness of an individual's fingerprint facilitates identification that is arduous to counterfeit, lessening the possibility of fraudulent activities and data manipulation. Ensuring the attendance data's unbreakable integrity enables direct amalgamation with the payroll framework, accelerating and simplifying the salary computation procedure. Furthermore, the introduction of a fingerprint attendance tool yields favourable outcomes including minimizing administrative expenses, boosting staff output, monitoring attendance in real-time, and promoting disciplinary behaviours. This attendance tool enables businesses to enhance their human resource management efficiency and enhance their employee work environment.